Restorative Treatment Patterns After Root Canal Obturation in Public Hospitals in Riyadh [Corrigendum] - AlSwayyed T; Bin Nafesah R; Alqutub M; Alfarhan A; Almashhaf A; Alshaikh H; Alhedeithi N (Dove Medical Press, 2022)
AlSwayyed T, Bin Nafesah R, Alqutub M, et al. Clin Cosmet Investig Dent. 2021;13:389–394. The authors have advised there is an error in the author list on page 389. The author name “Hessa Alshaikh” should read “Hussah Alshaikh”. The authors apologize for this error.